“Deservingness” and Public Support for Universal Public Goods: A Survey Experiment - Lastra Anadón, Carlos; Gift, Thomas (Oxford academic, 2023)
Voters support less spending on means-tested entitlements when they perceive beneficiaries as lacking motivation to work and pay taxes. Yet do concerns about the motivations of “undeserving” beneficiaries also extend to universal public goods (UPGs) that are free and available to all citizens? Lower spending on UPGs poses a particular trade-off: it lessens subsidization of “unmotivated” beneficiaries, but at the expense of reducing the ideal levels of UPGs that voters personally can access. Studies suggest that individuals will sacrifice their preferred amounts of public goods when beneficiaries who do not pay taxes try to access these goods, but it is unclear whether they distinguish based on motivations. To analyze this question, we field a nationally representative survey experiment in the UK that randomly activates some respondents to think about users of the country's universal National Health Service as either “motivated” or “unmotivated” noncontributors. Although effect sizes were modest and spending preferences remained high across the board, results show that respondents support less spending on the NHS when activated to think of users as “unmotivated” noncontributors. These findings suggest how the deservingness heuristic may shape public attitudes toward government spending, regardless of whether benefits are targeted or universal.